PENGGUNAAN CITRA LANDSAT 8 UNTUK PENDUGAAN VOLUME DAN SIMPANAN KARBON HUTAN: Studi Kasus KPHP Dampelas Tinombo Provinsi Sulawesi Tengah - , MISRAH; , Dr. Senawi, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Information on volume and carbon stocks can be obtained conventionally, which requires cost, power, and time, that it is necessary to acquire technology of Remote Sensing and GIS. The study aims to develop an estimator model for volume and forest carbon stocks by using Landsat 8 image to assume their distribution and abundance in KPHP Dampelas Tinombo. The research method is a supervised classification, vegetation index transformation, and field measurements. Determination of sample plots in the site based on the range of vegetation index values. Plot is random plots of 30m x 30 m. Correlation and Regression analysis applied to figure out the relationship between the vegetation index and the forest volume and carbon stocks. The results of the study is estimate model of volume Y = 531.26+354.26LnNDVI with a coefficient of determination (R2)of 0,604 and the estimate model of carbon stocks Y = 229.67+158.30LnNDVI with a coefficient of determination (R2) of 0.615. Volume at the high-density forests of 426.10 m3/ha, at medium-density forest of 258.45 m3/ha, and lowdensity forest of 91.30 m3/ha. Forest carbon stocks of 178.74 tons/ha at the highdensity forests, 103.97 tons/ha in medium-density forest, and 29.21 tons/ha in low-density forest. Total volume is 1,671,2407.03 m3 and total forest carbon stock is 15,126,821.76 tons. Key words: Landsat 8 image, Vegetation Index, Volume and carbon stocks